TECHNIQUES TO LEARN ENGLISH READING SKILLS EFFECTIVELY (Modern education and development, 2025)
This article explores the various strategies employed by effective readers throughout the stages of skimming, scanning, prediction- making, questioning, pre-reading, reading, and post-reading in language learning classrooms The study aims to discern the techniques utilized in both learning and teaching effective English reading skills. It emphasizes the importance of learners mastering techniques for efficiently skimming and scanning texts, as well as for making accurate predictions and posing insightful questions.